2009
DOI: 10.1084/jem.20081720
|View full text |Cite
|
Sign up to set email alerts
|

Priming of protective T cell responses against virus-induced tumors in mice with human immune system components

Abstract: Many pathogens that cause human disease infect only humans. To identify the mechanisms of immune protection against these pathogens and also to evaluate promising vaccine candidates, a small animal model would be desirable. We demonstrate that primary T cell responses in mice with reconstituted human immune system components control infection with the oncogenic and persistent Epstein-Barr virus (EBV). These cytotoxic and interferon-γ–producing T cell responses were human leukocyte antigen (HLA) restricted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
378
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 272 publications
(409 citation statements)
references
References 47 publications
29
378
2
Order By: Relevance
“…Both latent and lytic EBV antigen expression can be observed in infected HIS mice (Strowig et al, 2009;Chijioke et al, 2013;Tsai et al, 2013). Depending on the dose of EBV, it is possible to generate asymptomatic persistent infection or acute infectious mononucleosis-like symptoms, as well as lymphoproliferative disease in HIS mice (Yajima et al, 2008).…”
Section: Programs Of Ebv Infection In His Micementioning
confidence: 99%
See 3 more Smart Citations
“…Both latent and lytic EBV antigen expression can be observed in infected HIS mice (Strowig et al, 2009;Chijioke et al, 2013;Tsai et al, 2013). Depending on the dose of EBV, it is possible to generate asymptomatic persistent infection or acute infectious mononucleosis-like symptoms, as well as lymphoproliferative disease in HIS mice (Yajima et al, 2008).…”
Section: Programs Of Ebv Infection In His Micementioning
confidence: 99%
“…Depending on the dose of EBV, it is possible to generate asymptomatic persistent infection or acute infectious mononucleosis-like symptoms, as well as lymphoproliferative disease in HIS mice (Yajima et al, 2008). Latency III expressing cells can be found in all of these instances, as assessed by immunohistochemistry and in situ hybridization for EBV-encoded RNAs (EBERs), EBNA1, EBNA2, and LMP1 (Cocco et al, 2008;Strowig et al, 2009). However, it has been suggested that asymptomatic persistent infection without the massive lymphocyte expansion of infectious mononucleosis can also result in lower latency stages (Islas-Ohlmayer et al, 2004;Cocco et al, 2008;Ma et al, 2011).…”
Section: Programs Of Ebv Infection In His Micementioning
confidence: 99%
See 2 more Smart Citations
“…Primary infection as well as subsequent reactivation of the virus of EBV-infected B cells are tightly controlled by both CD8 1 and CD4 1 T cells [1,12]. Therefore, immunosuppressive therapy [13], hereditary immunodeficiencies [14] or immunocompromising HIV-infection [15] may lead to uncontrolled EBV reactivation and disease.…”
mentioning
confidence: 99%